Study of natural-ecological conditions in agro-landscapes based on field surveys and remote sensing - Hummatov, Nizami; Amanova, Shahnaz; Ahmadova, Asmar; Isgandarova, Ulviyya (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem definition. The number of undernourished people has dropped by almost half in the past two decades because of rapid economic growth and increased agricultural productivity. Under the conditions of climate change, natural and anthropogenic factors related to human activity lead to soil cover degradation, which leads to a decrease in soil fertility and ecosystem productivity, a deterioration in the socio-economic quality of human life, and generally creates serious problems in the country’s food security. Failure to take into account the agrophysical, agrochemical, physicochemical and other properties of soils in land use, depending on agroecological conditions, leads to the degradation of agricultural lands and manifests itself in the form of soil salinization, mechanical deformation and compaction, erosion, desertification, decreased productivity of ecosystems, and other forms. Therefore, in conditions of intensive land use, the management of the productivity of agrocenoses depends to one degree or another on the assessment of the agrophysical and agrochemical state of soils, which plays a decisive role in detecting and controlling degradation and making proposals for solving this problem. The purpose. The study was conducted in the cereal crops of the Lankaran-Astara (Jalilabad, Masalli, Lankaran) economic region of the Republic of Azerbaijan in the rainfed conditions with varying degrees of moisture. The study included cereal fields located in various rural areas of the administrative regions, as well as areas covering cereal crops of the Jalilabad Regional Experimental Station (RES) of the Research Institute of Crop Husbandry. Research methodology. In accordance with the methodology, the studies were conducted in the relevant departments and laboratories of the Research Institute of Crop Husbandry using space (GIS technologies, Earth remote sensing) and terrestrial (soil agrophysical and agrochemical properties, grain yield and quality indicators) methods. Conclusions. In terms of assessing the degree of erosion of soils, the structure vulnerability coefficient (KZ) is often used. KZ reflects the general structural quality of the soil in terms of its structural-aggregate composition. Structural degradation can lead to compaction and crusting of the soil surface, which reduces the rate of water infiltration, increases the risk of soil erosion and loss of the topsoil. The results show that the indicators characterizing the structural state of soils in all study regions (AVA, Kstr, Ds) can be assessed as “very good” (AVA >60%) and “good” (AVA >50%) according to the existing gradations. The trend of NDVI changes indicates that cereal crops are already in the full ripening phase in the Jalilabad region at the end of May and harvesting has begun.